2015
DOI: 10.1161/circoutcomes.8.suppl_2.174
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 174: Clinical Prediction Models for Cardiovascular Disease: The Tufts PACE CPM Database

Abstract: Background: Clinical prediction models (CPMs) estimate the probability of clinical outcomes and hold the potential to improve decision making and individualize care. For patients with cardiovascular disease (CVD) there are numerous CPMs available though the extent of this literature is not well described. Methods and Results: We conducted a systematic review for articles containing CPMs for CVD published between January 1990 through May 2012. CVD includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…Discrimination and calibration are both important characteristics in the evaluation of model performance; however, they remain underreported in the published medical literature. A systematic review addressing prediction models of cardiovascular outcomes noted that only 63% reported on discrimination and only 36% reported on calibration …”
Section: What Makes a Good Model?mentioning
confidence: 99%
“…Discrimination and calibration are both important characteristics in the evaluation of model performance; however, they remain underreported in the published medical literature. A systematic review addressing prediction models of cardiovascular outcomes noted that only 63% reported on discrimination and only 36% reported on calibration …”
Section: What Makes a Good Model?mentioning
confidence: 99%
“…These models ostensibly offer clinicians a way of assigning risk to individual patients to allow for precision management decisions and risk-adjusted reporting of performance measures. 1 An important performance measure for percutaneous coronary intervention (PCI) is postprocedure bleeding, which is not only the most common noncardiac complication after PCI but is also associated with increased mortality, morbidity, and cost. 2 Rao et al 3 developed a 31-variable risk prediction model, developed from data from the National Cardiovascular Data Registry (NCDR), that demonstrated reasonable model performance with a C statistic of 0.77.…”
mentioning
confidence: 99%
“…During the past decade, there has been a significant rise in the development of risk prediction models in cardiovascular disease. These models ostensibly offer clinicians a way of assigning risk to individual patients to allow for precision management decisions and risk-adjusted reporting of performance measures . An important performance measure for percutaneous coronary intervention (PCI) is postprocedure bleeding, which is not only the most common noncardiac complication after PCI but is also associated with increased mortality, morbidity, and cost .…”
mentioning
confidence: 99%
“…The abundance of currently available clinical prediction models (CPMs) has been demonstrated by a recent systematic review. 1 This review unearthed 796 scientific articles on the topic of CPMs and cardiovascular disease published from 1990 to 2012, with 90% being novel and the remainder recalibration or other adaptations of prior CPMs. Although utilization of CPMs is currently low, it promises to decrease use of the routine subjective eyeball test.…”
mentioning
confidence: 99%
“…The use of predictive analytics in modern cardiology has had a significant impact in decreasing the subjectivity of forecasting cardiovascular events. The abundance of currently available clinical prediction models (CPMs) has been demonstrated by a recent systematic review . This review unearthed 796 scientific articles on the topic of CPMs and cardiovascular disease published from 1990 to 2012, with 90% being novel and the remainder recalibration or other adaptations of prior CPMs.…”
mentioning
confidence: 99%